Recommendations for public safety zone within airport and observance of policy - Государська, І.Л. (Proceedings of National Aviation University, 2010)
10 year period aircraft accident summary is analysed in according to phase of flight in Ukraine. The impact probability model of aircraft is presented during take-off and landing as well take-off overrun and landing overrun at a specified point within airport. This model is based on Probability Density Functions. Development of land within Public Safety Zones of airport is recommended. Observance of policy of Public Safety Zones is given that based on documents ICAO.